REKOMENDASI STRATEGI PENGENDALIAN DENGUE DI KOTA BENGKULU TAHUN 2023-2025: FOCUS GROUP DISCUSSION (FGD) - Triana, Dessy; Gunasari, Lala Foresta Valentine; Martini, Martini; Suwondo, Ari; Sofro, Muchlis Achsan Udji (Universitas Bengkulu, 2025)
Dengue is a global health problem. There has been an increase in cases of more than 15 times over the last two decades. The causes of the rise in the number of cases and the increase in infected areas are very complex and multifactorial, including viral, vector, environmental, and human factors. A comprehensive prevention strategy is needed that includes all component factors that influence dengue disease to predict the incidence of the disease. This activity aimed to implement effective dengue control in Bengkulu City to reduce the number of dengue cases. The activity partners were the Bengkulu City Health Service, Bengkulu Provincial Health Service, Community Health Centers in Bengkulu City, and surveillance officers. The method of this activity was to focus group discussion to formulate a dengue control strategy in Bengkulu City for 2023-2025. The dengue control strategy that has been formulated can be implemented in the work area of ​​the community health center to reduce the number of dengue cases.